2017
DOI: 10.1097/pts.0000000000000397
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Obstetrical Hospitalist Program on the Safety Events in a Mid-Sized Obstetrical Unit

Abstract: Objective Because internal medicine hospitalist programs were developed to address issues in medicine such as a need to improve quality, improve efficiency, and decrease healthcare cost, obstetrical (OB) hospitalist models were developed to address needs specific to the obstetrics and gynecology field. Our objective was to compare outcomes measured by occurrence of safety events before and after implementation of an OB hospitalist program in a mid-sized OB unit. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A previous study also demonstrated a significantly eliminated obstetrical safety events from 11 to 0 following the OB hospitalist implementation[ 13 ]. Another previous study also proved that OB hospitalists could increase the vaginal birth after cesarean rate and decreased the C-section rate[ 14 ].…”
Section: Discussionmentioning
confidence: 88%
“…A previous study also demonstrated a significantly eliminated obstetrical safety events from 11 to 0 following the OB hospitalist implementation[ 13 ]. Another previous study also proved that OB hospitalists could increase the vaginal birth after cesarean rate and decreased the C-section rate[ 14 ].…”
Section: Discussionmentioning
confidence: 88%
“…[11][12][13][14] Another study demonstrated a decrease in obstetric safety events after implementation of an obstetric hospitalist program. 15 One area of concern in our specialty is the rising mortality rate in the United States, which seems to be rising fastest for women of color. [16][17][18] It has been postulated that Ob/Gyn hospitalists are well positioned to improve maternal mortality and its proxy, maternal morbidity.…”
mentioning
confidence: 99%
“…Other studies have shown a decrease in cesarean delivery rates and an increase in vaginal birth after cesarean rates with hospitalist programs 11–14 . Another study demonstrated a decrease in obstetric safety events after implementation of an obstetric hospitalist program 15 . One area of concern in our specialty is the rising mortality rate in the United States, which seems to be rising fastest for women of color 16–18 .…”
mentioning
confidence: 99%